BOLALAR ADABIYOTIDA ESTETIK TAFAKKUR VA BADIIY IFODA - Raximbayeva, Y.Sh. (SCIENCE and SOCIETY, 2025)
The article examines the problem of aesthetic thinking, its socio-psychological foundations and artistic embodiment in the works of Abdurakhmon Akbar, a representative of Uzbek children’s literature. Also, using specific examples, the artistic interpretation of children’s thoughts and feelings in the poet’s poetry is scientifically and theoretically analyzed.